Low expression of activation and inhibitory molecules on NK cells and CD4+ T-cells is associated with viral control (2015)
Chronic HIV-1 infection induces severe immune alterations, including hyperactivation, exhaustion, and apoptosis. In fact, viral control has been associated with low frequencies of these processes. Here, we evaluated the expression of activation.